Study of magnetic field behavior at lower pressure of neon in the axial phase of INTI plasma focus - Devi, K. K. A.; Saw, S. H.; Lee, P. C. K. (Maxwell Scientific Organization, 2014)
The magnetic field distribution substantially affects mechanisms for the generation of radiation in Z- pinches. Investigation of the axial component of the magnetic field is one of the important problems in plasma focus studies. The designed magnetic probe is intended to use for the study of current sheet in INTI plasma focus device with energy of about 3.3 kJ. The measurements of the azimuthal component of the magnetic field on the INTI Plasma Focus operated at neon pressures below 1 Torr was carried out using a custom built calibrated magnetic probe. The probe was tested for neon gas under the various lower pressures (i.e., 0.1, 0.3, 0.5 and 0.7, 1, 2, 3, 5 torr etc.). It is observed that the time response of the designed probe is sufficient for the rise time of the magnetic field associated with the current in the axial phase. We also note that the small size of the designed probe is well suited to sense the magnetic field without perturbing the plasma unduly. The probe designed and constructed is also suitable to carryout measurements to obtain axial distributions of trajectory, average axial velocity and magnetic field of the current sheath at a certain radial distances along the axis of the tube.